The influence of phytoestrogens on alleviating symptoms associated with menopause - Wiktoria Kotusiewicz; Nikola Siekierko; Maja Żołnierek; Mateusz Lewandowski; Ewa Gacoń; Julita Zembala; Brygida Zapała; Aldona Ząber; Jakub Kucharski; Jakub Świętochowski (Kazimierz Wielki University, 2023)
Introduction and purpose. Menopause causes complaints such as hot flashes, night sweats, sleep problems and vaginal dryness. Hormone replacement therapy (HRT) is an effective treatment option for women with moderate to severe symptoms. In women who are unable to undergo HRT, plant-based preparations containing phytoestrogens can be used as an alternative. The purpose of this paper is to summarize the effectiveness of phytoestrogen supplementation. State of knowledge. Phytoestrogens are natural compounds structurally similar to estrogens, such as estradiol. They are divided into different classes, including isoflavones and lignans. Isoflavones, including genistein, found in soy products, cause a significant reduction in the severity of hot flashes, as well as improvements in vaginal dryness and sexual function. Lignans, found in flaxseed, sesame seeds and whole grains, have effects similar to endogenous estrogens, but studies to date have not shown significant efficacy of this group of substances in reducing menopausal symptoms. Resveratrol, a naturally occurring compound found in grapes and berries, has a weak estrogenic effect, whereby several clinical trials have demonstrated the effectiveness of resveratrol supplementation in alleviating menopausal symptoms. Conclusions. Phytoestrogens have been shown to alleviate some symptoms of menopause, such as hot flashes and night sweats, and may also have positive effects on bone density and cognitive abilities. Effects may vary depending on the source, dose and duration of treatment. There are also potential risks associated with their use, for which reason more research is needed to fully understand their effectiveness and safety.